If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -5 = 2 + 22z Reorder the terms: -5 + 3z = 2 + 22z Solving -5 + 3z = 2 + 22z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-22z' to each side of the equation. -5 + 3z + -22z = 2 + 22z + -22z Combine like terms: 3z + -22z = -19z -5 + -19z = 2 + 22z + -22z Combine like terms: 22z + -22z = 0 -5 + -19z = 2 + 0 -5 + -19z = 2 Add '5' to each side of the equation. -5 + 5 + -19z = 2 + 5 Combine like terms: -5 + 5 = 0 0 + -19z = 2 + 5 -19z = 2 + 5 Combine like terms: 2 + 5 = 7 -19z = 7 Divide each side by '-19'. z = -0.3684210526 Simplifying z = -0.3684210526
| -8y-1=0 | | 18x^2+3x=10 | | 3(6-5x)=12x-36 | | 9c-c=112 | | 4z-6=-5+3z | | 6-2(3x-3)+6x=15x-5(3x+2) | | 3x-x=-5 | | 3(3+6)=2(x+4) | | 6b-45=57 | | 3z-19=-35+5z | | 3(3+6)=2(9+4) | | 14+6g-5=40 | | 5y-27=3y+2 | | 6(7u-u)+u=36+u | | 3(4z-2)=2Z-36 | | 3+4z+9=31 | | 8(y+6)=128 | | 3(2x-5)+4(x+2)=-7 | | x^5-2x^4-8x^3=0 | | 2(x+4)=38-4x | | 6v+32=-6+8(v+4) | | -5/8=g-1/4 | | 0.6x=28.3 | | -6(4n-6)-2n=-7n+17 | | y-4=6 | | h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x |